Analisis implementasi kebijakan anti-bullying di SMK: Hambatan dan solusi - Setiawan, Miftakhul Huda Dwi; Sidiq, Muhammad Arya; Hendriansyah, Yuda; Hastutiningsih, Arum Dwi (Journal of Smart Education and Learning, 2024)
This study analyzes the implementation of anti-bullying policies in Vocational High Schools (SMK), especially in identifying existing obstacles and solutions. The study employed a qualitative method with a case study approach, involving in-depth interviews with guidance and counseling teachers and subject teachers. The results of the study indicate that although anti-bullying policies, such as the formation of the Violence Prevention Team (TPK), have been implemented effectively, there are significant obstacles, such as limited human resources and victims' reluctance to report. Additionally, the large number of students poses a challenge in monitoring bullying-related activities. Strategic solutions include collaboration with external parties, such as psychologists from health centers, as well as prevention programs through anti-bullying awareness activities since grade 10. This study concludes that the success of the policy is highly dependent on effective coordination among teachers, staff, students, and parents, although some challenges still need to be addressed.